Estudo do comportamento da co-combustão da borra de café e do bagaço de cana-de-açúcar - Araújo, Dalila Medeiros de (2021)
With the unbridled growth of energy demand, the use based on fossil fuels has become a global problem. However, the search for sources that are less harmful to the environment began to intensify, and an alternative that has been adopted is the use of renewable sources, especially biomass. The work aimed to carry out the development of studies in international databases on the biomass co-combustion process, in addition to studying the co-combustion process of coffee grounds (BCF) and sugarcane bagasse (BCC), characterizing the physicochemical properties of these residues. To carry out the work, a bibliometric study was carried out using keywords in the Web of Science databases - Main Collection and Science Direct, analyzing the studies that addressed the chosen theme, as well as analyzes of the BCF and BCC through the characterizations physicochemical analysis of samples (immediate analysis, higher calorific value analysis and X-ray fluorescence) and thermogravimetric analysis. The results obtained showed that, through the literature review of the databases, studies on the subject are growing over the years, especially from 2016 to 2020, as it was also noted that in the vast majority of studies the co-combustion process was made between biomasses with coal and that with co-combustion the value of the activation energy (Ae) was lower than the combustion of each residue. The results of the immediate analysis showed that the levels of volatile material found both for the samples (BCF and BCC) and for the fixed carbon showed that there is a large amount of compounds that can be devolatilized, in addition to the values obtained from PCS BCF (18.34 MJ.kg-1) and BCC (18.05 MJ.kg-1) are comparable to traditional biomass fuels that have already been used for energy purposes. Through thermogravimetric analysis it was noted that the beginning of the thermal decomposition of BCF and BCC occurred in the range of 150 ºC, as well as that, in the oxidizing atmosphere, there was a thermal stability of the samples at lower temperatures. And regarding the co-combustion process, it was observed that the greatest mass loss occurs around 150 ºC to 350 ºC in all mixtures, and the mixture of 25% BCF with 75% BCC was the most reactive either by the Ignition temperature (Tig) (175 °C) and by the higher rate of mass loss at a lower temperature (25%.min-1 at 402 °C). Therefore, through this work it was possible to have an overview of the production of articles and that BCF and BCC biomass and their mixtures may have a good applicability in their use for energy purposes in combustion processes.